Cycloolefin polymer-based flexible printing wire material, preparation method and solar interface evaporator
By combining olefin metathesis ring-opening polymerization and ultraviolet curing with filler materials, a flexible cyclic olefin polymer-based printing filament suitable for FDM printing was prepared, which solved the contradiction between flexibility and strength and realized a high-efficiency solar interface evaporator with high evaporation efficiency and recyclability.
Patent Information
- Application Number
- CN202511866925.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-01-23
AI Technical Summary
In existing FDM printing material systems, the contradiction between the improved flexibility and decreased mechanical strength of cyclic olefin polymers remains unresolved, and they are difficult to adapt to FDM printing, resulting in insufficient material toughness and poor dimensional stability, making it difficult to meet the needs of wearable devices and flexible electronics.
By combining olefin metathesis ring-opening polymerization with UV curing, amino-terminated aniline trimers and other fillers are mixed with cyclic olefin polymers to form cyclic olefin composites suitable for FDM printing. The crosslinking density is controlled to prepare cyclic olefin polymer-based flexible printing filaments, and a biomimetic gradient pore structure is constructed by 3D printing.
The combination of high elasticity and dimensional stability was achieved, which improved the mechanical properties of the material. The prepared solar interface evaporator achieved an evaporation rate of 2.93 kg·m-2·h-1 under standard sunlight, with an efficiency of 95.11%, and is recyclable with stable performance.
Smart Images

Figure CN121379054A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fused deposition modeling (FDM) 3D printing filament preparation, specifically to cyclic olefin polymer-based flexible printing filaments and their preparation methods, and solar interface evaporators. Background Technology
[0002] Solar-driven interfacial evaporation (SDIE) technology utilizes solar energy and photothermal materials for seawater desalination and wastewater purification, and is considered one of the sustainable solutions to address freshwater scarcity. This technology achieves localized solar energy conversion at the gas-liquid interface through photothermal materials, minimizing heat loss and improving energy efficiency. However, the large-scale application of SDIE technology still faces several key challenges, including low evaporation efficiency, significant salt accumulation, difficulties in large-scale manufacturing, insufficient mechanical stability, poor resistance to contamination, and high costs. Moisture transport efficiency is a key factor affecting the evaporation efficiency of solar-driven interfacial evaporators (SDIEs), and can typically be achieved by adjusting the hydrophilicity and pore structure of the materials.
[0003] Traditional manufacturing processes such as manual assembly, template forming, aerogel preparation, and freeze drying have limitations in controlling structural precision, making it difficult to meet the demands of complex SDIE structures. In contrast, 3D printing (additive manufacturing) technology can precisely construct intricate structures and significantly improve equipment performance, particularly in salt resistance and operational stability. However, it still faces challenges in terms of large-scale production, sustainability, and cost-effectiveness. Meanwhile, although solar-driven interfacial evaporation technology is inherently green, most existing SDIEs are single-use and non-recyclable, leading to resource waste and environmental pollution. Fused deposition modeling (FDM) technology, with its widespread availability, ease of operation, and good material compatibility, has become the preferred solution for manufacturing precision structures. Currently, FDM printing materials are primarily rigid materials. Some commercially available FDM filaments improve flexibility by incorporating thermoplastic elastomers such as polyurethane (TPU) and polybutylene succinate (PBS) into rigid materials such as polylactic acid (PLA) and acrylonitrile-butadiene-styrene copolymer (ABS). However, these FDM filaments generally exhibit problems such as insufficient toughness, poor dimensional stability, and low temperature resistance, making it difficult to meet the stringent requirements of emerging industries such as wearable devices, soft robots, and flexible electronics for materials with high elasticity, dimensional stability, and weather resistance.
[0004] Cycloolefin compounds are polymerized into cyclic olefin polymers (COPs) through olefin metathesis or metallocene-catalyzed chemical reactions. Cycloolefin polymers have many advantages, including low shrinkage, low moisture absorption, low birefringence, flexibly adjustable glass transition temperature, excellent chemical resistance, and superior dielectric properties.
[0005] While some progress has been made in the flexible modification of COPs, two core issues remain unresolved: the contradiction between increased flexibility and decreased mechanical strength, and the lack of design for compatibility with FDM printing. Whether through chemical modification or physical blending, the introduction of flexible segments or elastomers disrupts the original rigid molecular chain network of COPs, leading to a significant decrease in material strength or weather resistance. Furthermore, current research largely focuses on improving the flexibility of COPs while neglecting their compatibility with FDM molding processes, resulting in "fibering" or decreased elastic recovery during polymer extrusion. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a cyclic olefin polymer-based flexible printing filament, its preparation method, and a solar interface evaporator.
[0007] This invention utilizes an olefin metathesis ring-opening polymerization reaction to form a cyclic olefin polymer from cyclic olefin monomers. Then, at least one of the following—amino-terminated aniline trimer (ACAT), carbon black, graphite, carbon nanotubes, graphene, and silica—is used as a filler. Under the action of a photoinitiator, the mixture of the cyclic olefin polymer and the filler is cured under ultraviolet light to form a cyclic olefin complex. Finally, a flexible printing filament based on the cyclic olefin polymer, suitable for FDM printing, is prepared by screw extrusion. This invention improves mechanical properties while maintaining flexibility by adding filler materials and combining them with an ultraviolet curing process to control the crosslinking density of the cyclic olefin complex.
[0008] This invention develops a flexible cyclic olefin polymer material containing filler that can be printed by FDM, and constructs a biomimetic gradient pore structure through fused deposition modeling (FDM) printing to prepare a solar interface evaporator with high water evaporation efficiency. This solves the core problems in solar interface evaporation technology, such as the difficulty in balancing evaporation efficiency and salt blockage, and the contradiction between high elasticity and dimensional stability of flexible device materials.
[0009] The COPs obtained by the olefin metathesis ring-opening polymerization reaction of this invention possess characteristics such as a balance of rigidity and flexibility, as well as being environmentally friendly, providing a solid foundation for the development of FDM filaments with high elasticity and dimensional stability. To achieve the above objectives, the technical solution of this invention is as follows.
[0010] The first aspect of this invention provides a method for preparing a cyclic olefin polymer-based flexible printing filament, comprising the following steps: A ring-opening polymerization reaction of cyclic olefin monomers is catalyzed by a Grubb catalyst to form a cyclic olefin polymer. Under the action of a photoinitiator, the mixture of the cyclic olefin polymer and the filler material is cured by ultraviolet light to obtain a cyclic olefin complex. The cyclic olefin complex is then extruded by a screw to prepare a cyclic olefin polymer-based flexible printing filament. The filler material is at least one of amino-terminated aniline trimer, carbon black, graphite, carbon nanotubes, graphene, and silicon dioxide.
[0011] Preferably, the cyclic olefin monomer is at least one selected from 2,3-dihydrofuran, 2,5-dihydrofuran, dicyclopentadiene, cyclooctene, and cyclooctadiene. The cyclic olefin monomer is preferably 2,3-dihydrofuran.
[0012] In this invention, the filler material can be any one or a mixture of amino-terminated aniline trimers, carbon black, graphite, carbon nanotubes, graphene, and silicon dioxide; preferably, it is an amino-terminated aniline trimer. In this invention, the filler material is primarily used to increase the stiffness of the filament; otherwise, printing would be impossible due to the matrix being too soft. Additionally, aniline trimers and other filler materials also serve as photothermal conversion materials, converting solar energy into thermal energy for water evaporation.
[0013] Preferably, the filler material accounts for 0.5% to 40% of the molar percentage of the cycloolefin monomer. The amount of filler material mainly affects the stiffness of the filament and the photothermal conversion efficiency.
[0014] Preferably, the Grubbs catalyst is a Grubbs I, Grubbs II, or Grubbs III catalyst; the preferred Grubbs catalyst is Grubbs II catalyst; the amount of Grubbs catalyst used is 1 / 100,000 to 10% of the molar percentage of the cycloolefin monomer. The amount of catalyst affects the molecular weight of the polymerization product, and ultimately affects the mechanical properties of the filament.
[0015] Preferably, the specific preparation method of the cyclic olefin complex is as follows: Grubb catalyst is dissolved in an organic solvent and then stirred with a mixture containing a photoinitiator and cyclic olefin monomers. The mixture is then subjected to olefin metathesis ring-opening polymerization catalyzed by the Grubb catalyst at 0°C to 100°C to form a cyclic olefin polymer. An organic solvent and filler are added and mixed thoroughly to obtain a final mixture. The mixture is then cured under ultraviolet light in the presence of a photoinitiator to obtain a cyclic olefin complex. In this invention, the polymerization temperatures of different cyclic olefin monomers vary. By selecting an appropriate temperature, the cyclic olefin monomers undergo olefin metathesis ring-opening polymerization to form the cyclic olefin polymer.
[0016] Preferably, the wavelength of the ultraviolet light is 350nm to 420nm, and the wavelength of the ultraviolet light is preferably 395nm. The ultraviolet curing time is 0.001h to 72h. The ultraviolet curing time is related to the thickness of the mixture. When the mixture is very thin, it can be completed in tens of seconds, while when it has a certain thickness, the time required is longer.
[0017] Preferably, the organic solvent is at least one selected from tetrahydrofuran, dichloromethane, and N,N-dimethylformamide, with tetrahydrofuran being the preferred organic solvent; the photoinitiator is any one selected from 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the photoinitiator is preferably 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. The amount of photoinitiator used is 0.05% to 5% of the molar percentage of the cyclic olefin monomer. Preferably, the amount of photoinitiator used is 1% to 5% of the molar percentage of the cyclic olefin monomer.
[0018] A second aspect of the present invention provides a cyclic olefin polymer-based flexible printing filament, which is prepared by the method described in the first aspect for preparing cyclic olefin polymer-based flexible printing filaments.
[0019] A third aspect of the present invention provides a solar interface evaporator, which is prepared by 3D printing using the cyclic olefin polymer-based flexible printing filament described in the second aspect.
[0020] Preferably, the solar interface evaporator has a gradient pore structure; the gradient pore structure is preferably a frustum-shaped pore structure; the pore inclination angle of the gradient pore structure is 0° to 90°. The pore inclination angle of the gradient pore structure is preferably 68° to 84°.
[0021] The beneficial effects of this invention are: 1. This invention employs a Grubb catalyst to catalyze the ring-opening polymerization of cyclic olefin monomers, forming a cyclic olefin polymer. The cyclic olefin polymer is then mixed with a filler material and cured under ultraviolet light in the presence of a photoinitiator to obtain a cyclic olefin composite. This composite is then extruded using a screw extruder to prepare a flexible cyclic olefin polymer-based printing filament suitable for FDM printing. This invention, by adding filler material and combining it with an ultraviolet curing process, controls the crosslinking density of the cyclic olefin composite, thereby improving mechanical properties while maintaining flexibility.
[0022] 2. This invention develops a cyclic olefin polymer material containing filler that can be printed by FDM and constructs a biomimetic gradient pore structure. A solar interface evaporator with high water evaporation efficiency is prepared by fused deposition modeling 3D printing process. This solves the core problems in solar interface evaporation technology, such as the difficulty in balancing evaporation efficiency and salt blockage, and the contradiction between high elasticity and dimensional stability of flexible device materials.
[0023] 3. The cyclic olefin polymer-based flexible printing filament of this invention enables the 3D printing of an integral solar interface evaporator with a gradient pore structure. By precisely controlling the pore angle, pore size, and evaporator thickness, the efficient production of an integral self-floating evaporator with complex geometries is achieved. The solar interface evaporator prepared by this invention can achieve a surface temperature of 55°C under standard sunlight intensity irradiation, with an evaporation rate of 2.93 kg·m³. -2 ·h -1 The efficiency is as high as 95.11%. The solar interface evaporator of this invention did not show salt precipitation after 30 days of continuous operation, and its performance was stable.
[0024] 4. The cyclic olefin polymer-based flexible printing filament of this invention can be recycled. Analysis after multiple recycling cycles shows that the molecular structure, thermal properties, and mechanical properties of the material remain essentially unchanged. The solar interface evaporator made from the recycled filament using 3D printing exhibits evaporation performance almost identical to that of the original solar interface evaporator. This cyclic olefin polymer-based flexible printing filament achieves a synergistic integration of high efficiency, salt resistance, and closed-loop recycling, laying an important technical foundation for large-scale solar-driven interface water evaporation technology. Attached Figure Description
[0025] Figure 1 Images show the front and back of a 3D-printed solar interface evaporator with a gradient pore structure. Image A is the front view of the solar interface evaporator; image B is the back view.
[0026] Figure 2 The infrared spectrum of the PDHF-6%ACAT composite material prepared in Example 1 is shown.
[0027] Figure 3 The image shows the X-ray photoelectron spectrum of the PDHF-6%ACAT composite material prepared in Example 1.
[0028] Figure 4 The viscosity of the PDHF-6%ACAT printing filament prepared in Example 1 varies with shear rate at different temperatures.
[0029] Figure 5 Images are of solar interface evaporators with different tilt angles. Among them, A is an image of PDHF-4%ACAT-F(84); B is an image of PDHF-4%ACAT-F(78); and C is an image of PDHF-4%ACAT-F(68).
[0030] Figure 6The results of salt resistance tests for solar interface evaporators with different tilt angles in Example 7 are shown. Among them, a1 to a5 are the salt resistance test results of PDHF-4%ACAT-F (90) at 0 min, 15 min, 30 min, 1 h and 2 h, respectively; b1 to b5 are the salt resistance test results of PDHF-4%ACAT-F (68) at 0 min, 5 min, 10 min, 15 min and 20 min, respectively; c1 to c5 are the salt resistance test results of PDHF-4%ACAT-F (84) at 0 min, 15 min, 30 min, 45 min and 1 h, respectively.
[0031] Figure 7 The figures show the water evaporation rate curves over time for solar interface evaporators with different tilt angles in Example 7, as well as the water evaporation rate bar charts and efficiency curves for PDHF-4%ACAT-F(84) with different thicknesses. Specifically, A represents the water evaporation rate curves over time for solar interface evaporators with different tilt angles; B represents the water evaporation rate bar charts and efficiency curves for PDHF-4%ACAT-F(84) with different thicknesses.
[0032] Figure 8 The evaporation rate of solar interface evaporators with different ACAT contents varies with time.
[0033] Figure 9 The surface temperature change of PDHF-4%ACAT-F(84) under a standard solar radiation intensity is shown in the figure.
[0034] Figure 10 The ultraviolet absorption spectrum of PDHF-6%ACAT-F(84) is shown.
[0035] Figure 11 The results are from the water evaporation rate stability test of PDHF-6%ACAT.
[0036] Figure 12 The results of outdoor testing of SGIE PDHF-6%ACAT-F(84) are as follows.
[0037] Figure 13 The graph shows the changes in water evaporation rate and surface temperature of the solar interface evaporator before and after recycling. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0039] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] This invention provides a method for preparing a flexible cyclic olefin polymer-based filament suitable for FDM printing. The method involves ring-opening polymerization of cyclic olefin monomers to form a cyclic olefin polymer via olefin metathesis. At least one of amino-terminated aniline trimer (ACAT), carbon black, graphite, carbon nanotubes, graphene, and silica is used as a filler material. Under the action of a photoinitiator, the mixture of the cyclic olefin polymer and the filler material is cured under ultraviolet light to form a cyclic olefin composite. Finally, the composite is obtained by screw extrusion to produce a flexible cyclic olefin polymer-based filament suitable for FDM printing, applicable to the fabrication of complex solar interface evaporators using 3D printing. This invention utilizes filaments prepared with amino-terminated aniline trimer as filler to fabricate monomeric self-floating solar interface evaporators (SDIEs) consisting of a single-layer photothermal layer. The pore structure exhibits a gradient pore structure, narrower at the top and wider at the bottom, as shown below. Figure 1 As shown. This invention, through the integration of rational material and structural design, achieves efficient water transport and efficient salt separation, providing a feasible solution for developing high-performance, durable, and sustainable solar-driven interfacial evaporation systems.
[0041] This invention utilizes a 3D-printed frustum-shaped porous structure to enhance capillary-driven water transport and gravity-assisted salt reflux, achieving simultaneous high evaporation rates and continuous salt removal. The SGIE reaches 2.93 kg·m³ under standard sunlight irradiation. -2 ·h -1 The evaporator achieves an evaporation rate of 95.1% and operates stably for 30 days in a 3.5 wt% sodium chloride solution without salt accumulation. Furthermore, the evaporator is fully recyclable without performance degradation. This closed-loop strategy organically combines structural design, intelligent manufacturing, and material reuse, providing a solution for the sustainable and large-scale application of solar-driven interfacial evaporation technology.
[0042] The technical solution of the present invention will be further described below through specific embodiments. In the following embodiments, unless otherwise specified, the methods described are conventional methods; the reagents and materials described are commercially available unless otherwise specified. In the following embodiments, the synthesis method of the photothermal material ACAT is based on Reference 1: Chen, Q. et al., A durable monolithic polymer foam for efficient solar steam generation; Chemical Science 9, 623-628, (2018).
[0043] 2,3-Dihydrofuran, 2,5-Dihydrofuran, dicyclopentadiene, cyclooctene and cyclooctadiene (monomers), Grubbs catalyst, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator) were all purchased from commercial suppliers and used directly without further purification.
[0044] Example 1 A method for preparing a cyclic olefin polymer-based flexible printing filament includes the following steps: Step 1, Synthesis of amino-terminated aniline trimer for photothermal materials: Refer to Reference 1: Chen Qiaomei et al., A durable monolithic polymer foam for efficient solar steam generation; Chemical Science 9, 623-628, (2018). The specific preparation process is as follows: First, 16.0 mmol of aniline and 16.0 mmol of 4,4'-diaminodiphenylamine sulfate were dissolved in an aqueous hydrochloric acid solution (1M, 150 mL) containing 15 g of NaCl to obtain a first solution. Then, 16.0 mmol of ammonium persulfate was dissolved in an aqueous hydrochloric acid solution (1M, 25 mL) using a dropping funnel at 5 °C to obtain a second solution. The second solution was added to the first solution, and the resulting mixture was stirred at 5 °C for 1 hour. The precipitate was collected by filtration and washed with an aqueous hydrochloric acid solution (1M, 150 mL). Subsequently, the filter cake was added to an aqueous ammonia solution (1M, 300 mL) and stirred for 12 hours. The mixture was then filtered again and washed with a large amount of distilled water. A black powder was finally obtained and dried in a vacuum oven at 60 °C for 3 hours to obtain the amino-terminated aniline trimer, denoted as ACAT.
[0045] Step 2, Preparation of PDHF-6%ACAT composite material: 10 mg of Grubbs II catalyst was dissolved in 1.5 mL of anhydrous tetrahydrofuran, and then added to a mixture containing 428 mg TPO and 123 mmol of 2,3-dihydrofuran. The mixture was stirred at 40 °C for 2 h to catalyze the ring-opening polymerization of 2,3-dihydrofuran (DHF) using the Grubbs II catalyst, forming the cyclic olefin polymer PDHF (poly(2,3-dihydrofuran)). Subsequently, the cyclic olefin polymer PDHF was diluted with 100 mL of anhydrous tetrahydrofuran, and 7.4 mmol of photothermal material ACAT was added and mixed thoroughly. The solvent was removed under reduced pressure to obtain the final mixture.
[0046] The mixture was placed in a UV curing system and cured under UV light at a wavelength of 395 nm for 2 hours to obtain a black cyclic olefin composite, namely the PDHF-6%ACAT composite material; wherein ACAT accounts for 6% of the molar percentage of 2,3-dihydrofuran.
[0047] Step 3, Preparation of cyclic olefin polymer-based flexible printing filaments: PDHF-6%ACAT composite material was used to prepare cyclic olefin polymer-based flexible printing filaments via a twin-screw extruder. The three temperature zones of the twin-screw extruder were set to 90℃, 120℃, and 145℃, respectively.
[0048] Example 2 A method for preparing a cyclic olefin polymer-based flexible printing filament differs from Example 1 in that ACAT accounts for 4% of the molar percentage of 2,3-dihydrofuran; the specific preparation method includes the following steps: Step 1, Synthesis of the photothermal material ACAT: Reference 1: Chen, Q. et al., A durable monolithic polymer foam for efficient solar steam generation; Chemical Science 9, 623-628, (2018). Step 2, Preparation of PDHF-4%ACAT composite material: 10 mg of Grubbs II catalyst was dissolved in 1.5 mL of anhydrous tetrahydrofuran, and then added to a mixture containing 428 mg TPO and 123 mmol 2,3-dihydrofuran. The mixture was stirred at 40 °C for 2 h to catalyze the ring-opening polymerization of 2,3-dihydrofuran (DHF) using the Grubbs II catalyst, forming the cyclic olefin polymer PDHF. Subsequently, the cyclic olefin polymer PDHF was diluted with 100 mL of anhydrous tetrahydrofuran, and the photothermal material ACAT was added and mixed thoroughly. The solvent was removed under reduced pressure to obtain the final mixture.
[0049] The mixture was placed in a UV curing system and cured under UV light at a wavelength of 395 nm for 2 hours to obtain a black cyclic olefin composite, namely the PDHF-4%ACAT composite material; wherein ACAT accounts for 4% of the molar percentage of 2,3-dihydrofuran.
[0050] Step 3, Preparation of cyclic olefin polymer-based flexible printing filament: A cyclic olefin polymer-based flexible printing filament, denoted as PDHF-4%ACAT printing filament, was prepared from the PDHF-4%ACAT composite material using a twin-screw extruder. The temperatures of the three zones of the twin-screw extruder were set to 90℃, 120℃, and 145℃, respectively.
[0051] Example 3 A method for preparing a cyclic olefin polymer-based flexible printing filament differs from Example 1 in that ACAT accounts for 5% of the molar percentage of 2,3-dihydrofuran; the prepared cyclic olefin polymer-based flexible printing filament is designated as PDHF-5%ACAT printing filament, where ACAT accounts for 5% of the molar percentage of 2,3-dihydrofuran.
[0052] Example 4 A method for preparing a cyclic olefin polymer-based flexible printing filament differs from Example 1 in that ACAT accounts for 7% of the molar percentage of 2,3-dihydrofuran; the prepared cyclic olefin polymer-based flexible printing filament is designated as PDHF-7%ACAT printing filament, where ACAT accounts for 7% of the molar percentage of 2,3-dihydrofuran.
[0053] Example 5 A method for preparing a cyclic olefin polymer-based flexible printing filament differs from Example 1 in that ACAT accounts for 8% of the molar percentage of 2,3-dihydrofuran; the prepared cyclic olefin polymer-based flexible printing filament is designated as PDHF-8%ACAT printing filament, where ACAT accounts for 8% of the molar percentage of 2,3-dihydrofuran.
[0054] The cyclic olefin polymer-based flexible printing filaments prepared in Examples 1 to 5 are denoted as PDHF-x%ACAT printing filaments, where x = 4 to 8, and x represents the molar percentage of ACAT in 2,3-dihydrofuran. PDHF-x%ACAT printing filaments can be used to prepare solar interface evaporators.
[0055] Test 1: Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and shear viscosity test.
[0056] Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy were performed on the PDHF-6%ACAT composite material prepared in Example 1 to confirm the chemical structure of the PDHF-6%ACAT composite material. Figure 2 The infrared spectrum of the PDHF-6%ACAT composite material prepared in Example 1 is shown. Figure 3 The image shows the X-ray photoelectron spectrum of the PDHF-6%ACAT composite material prepared in Example 1. Figure 2 and Figure 3 The results showed that the PDHF-6%ACAT composite material was successfully prepared. Subsequent tests using Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy on the PDHF-x%ACAT composite materials prepared in Examples 2–5 confirmed the successful preparation of the PDHF-x%ACAT composite material.
[0057] The shear viscosity of the PDHF-x%ACAT printing filaments prepared in Examples 1 to 5 was tested using a rheometer. Figure 4 The viscosity of the PDHF-6%ACAT printing filament prepared in Example 1 varies with shear rate at different temperatures. Figure 4 Shear viscosity data show that PDHF-x%ACAT printing filament has significant shear thinning and temperature-sensitive properties, which gives it a unique advantage in 3D printing applications.
[0058] Example 6 A method for preparing a solar interface evaporator includes the following steps: The PDHF-6%ACAT composite material from Example 1 was used to prepare a cyclic olefin polymer-based flexible printing filament, denoted as PDHF-6%ACAT printing filament, via a twin-screw extruder. Then, an integral solar interface evaporator with a truncated quadrangular pore structure, denoted as SGIEs, was fabricated using 3D printing. Specific printing parameters were: nozzle diameter 0.5 mm; printing temperature 180℃~200℃.
[0059] The method for constructing the truncated pyramidal porous structure is as follows: the first segment has a layer height of 0.4 mm, and all subsequent segments have a layer height of 0.5 mm, with each segment employing a two-layer structure. A linear filling pattern is used, with an initial spacing of 1 mm, which is then gradually increased by 0.4 mm for each segment, thereby adjusting the tilt angle of the truncated pyramidal pores to 84°. Each segment undergoes two 90-degree rotations to form a grid-like porous structure, resulting in a truncated pyramidal pore structure with an tilt angle of 84°. o A solar interface evaporator with a truncated quadrangular gradient pore structure is designated as PDHF-6%ACAT-F(84).
[0060] Example 7 A method for preparing a solar interface evaporator includes the following steps: The PDHF-4%ACAT composite material from Example 2 was used to prepare a cyclic olefin polymer-based flexible printing filament, denoted as PDHF-4%ACAT printing filament, via a twin-screw extruder. Then, an integral solar interface evaporator with a gradient truncated pyramidal pore structure, denoted as SGIEs, was fabricated using 3D printing. Specific printing parameters were as follows: nozzle diameter 0.5 mm; printing temperature 180℃~200℃; initial layer height 0.4 mm, subsequent layer height 0.5 mm, with each segment employing a two-layer structure. A linear filling mode was used, with an initial spacing of 1 mm, followed by progressive increases of 0.1 mm, 0.2 mm, 0.4 mm, or 0 mm for each segment, thereby adjusting the tilt angle of the pyramidal cross-section pores to 68°, 78°, 84°, or 90°. Each segment underwent two 90-degree rotations to form a grid-like pore structure, resulting in solar interface evaporators with different gradient pore structures. Example 7 prepared four different gradient pore structures, denoted as PDHF-4%ACAT-F (68), PDHF-4%ACAT-F (78), PDHF-4%ACAT-F (84), and PDHF-4%ACAT-F (90), respectively. Figure 5 As shown.
[0061] Example 8 A method for preparing a solar interface evaporator is carried out according to the method for preparing a solar interface evaporator in Example 6, except that the cyclic olefin polymer-based flexible printing filament is the PDHF-5%ACAT printing filament of Example 3.
[0062] Example 9 A method for preparing a solar interface evaporator is carried out according to the method for preparing a solar interface evaporator in Example 6, except that the cyclic olefin polymer-based flexible printing filament is the PDHF-7%ACAT printing filament of Example 4.
[0063] Example 10 A method for preparing a solar interface evaporator is carried out according to the method for preparing a solar interface evaporator in Example 6, except that the cyclic olefin polymer-based flexible printing filament is the PDHF-8%ACAT printing filament of Example 5.
[0064] While maintaining the top cross-sectional dimensions and ACAT content (4%) unchanged, Example 7 of this invention prepared three different gradient pore structures: PDHF-4%ACAT-F (68), PDHF-4%ACAT-F (78), and PDHF-4%ACAT-F (84); simultaneously, a vertical quadrangular prism pore structure, PDHF-4%ACAT-F (90), was also prepared. Two geometric structures were fabricated for the SGIEs of Examples 6 to 10 of this invention: a disc (diameter Ø8 cm) for salt corrosion and condensation tests, and a square specimen (8 mm × 8 mm) for evaporation and cycling performance evaluation. The thickness of the SGIEs can be changed by adjusting the number of segments.
[0065] Test 2: Salt resistance and evaporation performance test.
[0066] like Figure 6 The salt tolerance and self-cleaning ability of the SGIEs from Example 7 were evaluated by flocculating them on distilled water and depositing 0.5 g of sodium chloride particles on their surface. Figure 6 As shown in a1 to a5, the amount of sodium chloride dissolved on PDHF-4%ACAT-F (90) was negligible within 2 hours. In contrast, the sodium chloride on PDHF-4%ACAT-F (68) dissolved almost completely within 20 minutes. Figure 6 b1 to b5. PDHF-4%ACAT-F(84) requires approximately 1 hour to dissolve completely, such as... Figure 6 c1 to c5. The results show that the gradient pore structure significantly enhances the water transport and salt repulsion capabilities of SDIEs, thereby achieving better self-cleaning performance.
[0067] Under 1 hour of standard sunlight, the water evaporation rate of PDHF-4%ACAT-F(θ) (θ represents the tilt angle) in Example 7 increased as the opening angle of the truncated pyramid decreased, such as Figure 7 As shown in Figure A, the maximum value (PDHF-4%ACAT-F(84)) is reached at an inclination angle of 84°. This is mainly because the smaller the opening angle of the pyramidal cross section, the smaller the local radius of the pores, thereby promoting capillary-driven water transport. In order to achieve the best balance between salt tolerance and evaporation performance, the inclination angle of the pyramidal pores was finally set to 84°.
[0068] Evaporation efficiency measurement: The experimental setup included a SOL3A solar simulator (Newport Oriel Sol3A™, equipped with a 300W xenon lamp and AM 1.5G filter), an electronic balance (Mettler Toledo ME204E, accuracy 0.1mg), a custom-designed test chamber, and a computer data acquisition system. Solar irradiance was calibrated to 1 kW·m using a standard silicon reference cell. -2 The apparatus was stabilized for 30 minutes before formal measurements. Given the limited irradiation area of the solar simulator, a polystyrene foam-insulated quartz cuvette (10mm×10mm×50mm) was used as the evaporation chamber to minimize convective and conductive heat loss. The experimental setup was placed on an analytical balance, which transmitted mass data to a computer in real time for continuous monitoring of the evaporation rate. Simultaneously, an infrared thermal imager (hikmicro H16, measurement accuracy ±2%) was used to record the surface temperature distribution of the evaporator. All experiments were conducted under controlled laboratory conditions: ambient temperature 26±2℃, relative humidity 52±2%.
[0069] For ease of description, the solar interface evaporator is simply referred to as an evaporator. The water evaporation efficiency of the evaporator can be calculated using the following formula: η = ṁE equ / C opt P 0; where η represents the water evaporation efficiency of the evaporator, % ṁ This indicates the water evaporation rate of the evaporator, expressed in kg / (m³). 2 ·h); E equ This represents the equivalent enthalpy of vaporization of water in the corresponding evaporator; C opt This represents optical concentration, which is a dimensionless parameter. P 0 represents solar power intensity; ṁE equ This indicates the actual power consumed during the water evaporation process; C opt P 0 represents the actual solar radiation power received by the evaporator surface after optical adjustment.
[0070] Based on the law of conservation of energy, the equivalent enthalpy is determined by comparing the evaporation rates of bulk water and SGIEs under dark conditions: E equ m e = E 0 m 0; where, 2450 J g -1 The theoretical enthalpy of evaporation, This represents the evaporation rate of the bulk water in the dark. This corresponds to the evaporation rate of the evaporator in the dark.
[0071] The thickness of solar interface evaporators (SGIEs) plays a crucial role in regulating water transport distance and heat conduction. SGIEs with thicknesses ranging from 3 mm to 9 mm were fabricated using 3D printing technology while maintaining a constant pore inclination angle of 84° for the gradient truncated pyramid pore structure. The pure water evaporation rate initially increased and then decreased with increasing thickness, as shown in the figure. Figure 7 As shown in Figure B, the evaporation rate and efficiency peak at a thickness of 5 mm, at which point the evaporation rate and efficiency reach 2.41 kg / (m²). 2 ·h) and 90.6%.
[0072] Evaporation rates of SGIEs with different ACAT contents were measured, such as... Figure 8 As the ACAT content increased from 4% to 8%, the water evaporation rate showed a trend of first increasing and then decreasing, with optimal performance observed at an ACAT content of 6%. Under standard sunlight intensity, the surface temperature of SGIEs rapidly increased from ambient temperature of 26.4℃ to 41.5℃ within 1 minute, reached 50.4℃ within 10 minutes, and stabilized at around 55℃ after 1 hour. Figure 9 The optimal structural parameters for SGIEs were ultimately determined to be: a pyramidal pore shape with an inclination angle of 84°, a thickness of 5 mm, and an ACAT content of 6%. These optimized parameters achieved a yield of 2.93 kg / m³. 2 It boasts a remarkable evaporation rate of / h and an efficiency of 95.1%.
[0073] Test 3: Hydrophilicity characterization of 3D printed SGIEs.
[0074] According to the Jurin-Laplace formula, the higher the hydrophilicity of a material (i.e., the stronger the hydrophilicity, the stronger the binding ability of water molecules), the change in the contact angle significantly increases the capillary rise height of water molecules in the pores of SGIEs materials, thereby enhancing the water flow rinsing effect and improving the salt resistance of the material.
[0075] The contact angles of PDHF-6%ACAT-F(84) and its 3D-printed precursor PDHF-6%ACAT composite were measured. The initial contact angle of the printed PDHF-6%ACAT-F(84) was 69.44°, and that of the precursor PDHF-6%ACAT composite was 87.25°. After a 10-minute drying process, the contact angles decreased to 58.42° and 74.42°, respectively. This improvement in wettability is attributed to the hydrogen bonding between water molecules and oxygen atoms in the PDHF backbone. Furthermore, the micro-roughness and pore distribution introduced by the 3D printing process further enhance the hydrophilic properties of the material surface.
[0076] Test 4: Broadband light absorption capability analysis.
[0077] High-performance broadband solar absorption and efficient thermal management are key to improving the evaporation efficiency of single-component solar collectors (SGIEs). ACAT materials have been proven to have excellent photothermal properties, but to fully realize their potential, a suitable substrate material is still needed. Introducing PDHF not only significantly improves the hydrophilicity of the composite material but also greatly enhances its broadband light absorption capability. For example... Figure 10 As shown, the PDHF-6%ACAT-F(84) material exhibits an absorption rate of over 98% in the wavelength range of 250nm to 2250nm.
[0078] Test 4: Water treatment performance analysis.
[0079] Figure 11 The performance of SGIE PDHF-6%ACAT-F(84) in seawater desalination and wastewater treatment was demonstrated. The water evaporation rate gradually decreased with increasing salinity, but maintained significant stability under high salinity conditions: reaching 2.93 kg·m³ in pure water (0 wt% sodium chloride). -2 ·h -1 In simulated seawater (3.5 wt% sodium chloride), the concentration reached 2.68 kg·m³. -2 ·h -1 In high-salinity brine (20wt% sodium chloride), the concentration reaches 2.26 kg·m³. -2 ·h -1 The apparatus was used to collect condensate, and the Na in the condensate was quantitatively analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES). + K + Ca 2+ and Mg 2+ Concentration. Compared to the initial brine, the concentrations of these four ions in the desalinated water decreased by two to three orders of magnitude, with removal efficiencies of 99.99% (Na+, Na ... + ), 99.97% (K + ), 99.58% (Ca2+ ) and 99.98% (Mg 2+ All values were well below the drinking water standard threshold. SGIE PDHF-6%ACAT-F(84) exhibited excellent salt tolerance, with no visible sodium chloride crystals observed even after long-term operation in high-salinity brine. This performance can be attributed to its gradient pore structure, which facilitates gravity-driven salt reflux and effectively inhibits salt accumulation at the evaporation interface. Under standard solar radiation, SGIEs (SGIE PDHF-6%ACAT-F(84)) maintained a salt tolerance of approximately 2.68 kg·m³ after 30 days of continuous operation in a 3.5 wt% sodium chloride solution. -2 ·h -1 The stable evaporation rate was achieved. The daily evaporation rate for the first 10 days ranged from 2.56 to 2.77 kg·m³. -2 ·h -1 Fluctuations within a certain range, with no obvious downward trend observed, such as Figure 11 After six months of storage, SGIEs maintained nearly identical evaporation performance across all brine concentrations, demonstrating their superior long-term stability and operational durability.
[0080] In addition to desalination, PDHF-6%ACAT-F(84) can also effectively remove organic dyes and heavy metal ions from wastewater, realizing the recycling of water resources. This evaporator is effective in removing organic dyes and heavy metal ions from wastewater containing three common organic dyes (methylene blue, methyl orange, and rhodamine B) and their mixtures, as well as wastewater containing heavy metal ions (Zn). 2+ Cd 2+ Cr 3+ The tests were conducted on wastewater containing both the wastewater sample and its mixture. Under standard solar irradiation conditions, the evaporation rate of both wastewaters remained stable at approximately 2.75 kg·m³. -2 ·h -1 Compared to the slight decrease in pure water, this is attributed to the reduction in saturated vapor pressure due to the dissolution of solutes. Ultraviolet-visible spectroscopy (UV-Vis) analysis confirmed that organic dyes were almost completely removed, and the purified water showed no obvious absorption peaks and was visually clear and transparent. Inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis showed that the concentration of heavy metal ions decreased by 4 to 5 orders of magnitude, with a removal efficiency of 99.98% (Zn... 2+ ), 99.99% (Cd 2+ ) and 99.97% (Cr 3+ All final concentrations were far below the World Health Organization's drinking water standards. These results fully demonstrate that PDHF-6%ACAT-F(84) not only has excellent treatment capabilities for dye and heavy metal wastewater, but also produces pure water that fully meets the standards for direct drinking water.
[0081] Test 5: Outdoor test of evaporation performance.
[0082] The evaporation performance of SGIE PDHF-6%ACAT-F(84) was evaluated under real outdoor conditions, such as... Figure 12 The outdoor experiment was conducted on August 27, 2024, on the campus of Sichuan Normal University in Chengdu, China. During continuous monitoring from 9:00 AM to 5:00 PM, residual water volume, solar radiation flux, ambient humidity, and ambient temperature were tracked. Water vapor began to form within one minute of activation, and condensation began to accumulate in the storage chamber after approximately 40 minutes. During the period of strongest solar radiation (11:00 AM to 2:00 PM), the solar radiation flux remained stable at approximately 0.8 kW·m². -2 The evaporator reached its maximum evaporation rate of 2.88 kg·m³. -2 ·h -1 It is worth noting that the outdoor solar radiation flux is lower than the standard 1 sun (1 kW·m²). -2 However, the outdoor evaporation rate (2.88 kg·m³) -2 ·h -1 (It) remains stable, such as Figure 12 This value is slightly higher than the laboratory measurement (2.68 kg·m). -2 ·h -1 This improvement stems from the synergistic effect of increased ambient temperature and decreased humidity, which together reduce the enthalpy of vaporization and enhance interfacial water diffusion, thus offsetting the reduction in solar radiation input. These results indicate that PDHF-6%ACAT-F(84) maintains excellent evaporation performance under actual operating conditions and has broad application prospects.
[0083] Test 6: Recyclability Analysis.
[0084] Used SGIEs can be recycled without pretreatment. Specifically, the used SGIEs are cut into fragments and directly reloaded into the 3D printer's barrel, and the solar interface evaporator is reprinted using the same parameters. This "recycling-reprinting" cycle is repeated five times. The photothermal conversion temperature and water evaporation rate of the recycled SGIE materials are evaluated, such as... Figure 13 .
[0085] The results showed that the SGIEs prepared after five cycles maintained structural integrity and did not collapse. During the 3D printing process, the filament was extruded uniformly without breakage, confirming that the recycled material is fully suitable for 3D printing. Under standard sunlight intensity irradiation at 1 hour intervals, the surface temperature remained stable at approximately 55.7°C throughout all cycles, consistent with the original evaporator temperature. The evaporation rate remained stable, with a minimum value of 2.85 kg·m³. -2 ·h -1 ,like Figure 13 .
[0086] In summary, SDIEs (Self-Drying Water Extraction Systems) technology, as a green and sustainable solution to address freshwater scarcity, has long been limited in its large-scale application due to the inherent contradiction between water evaporation efficiency and salt tolerance. Overcoming this technological bottleneck requires synergistic optimization of energy input, water transport, thermal management, and salt rejection. This invention proposes an innovative solution integrating structural design, material selection, manufacturing processes, and recyclability. By constructing a gradient truncated pyramidal pore structure and optimizing the pore tilt angle, pore size, and pore height, a synergistic mechanism of "bottom-up water supply and top-down capillary reverse transport" is formed. This design not only improves water transport efficiency but also utilizes gravity-driven brine recirculation along the inclined pore walls, while simultaneously achieving salt crystallization through buffer spaces, thus achieving a dynamic balance between water supply, evaporation, and salt rejection.
[0087] In terms of materials, this invention has developed a high-efficiency composite material, PDHF-6%ACAT, using ACAT as the photothermal component and hydrophilic PDHF as the substrate, synthesized through an olefin metathesis ring-opening polymerization reaction. This composite material, with its hierarchical porous structure, significantly improves solar energy absorption efficiency and reduces thermal conductivity, thereby minimizing heat loss.
[0088] In terms of manufacturing process, this invention employs high-temperature screw extrusion 3D printing technology to precisely control the pore angle, pore diameter, and evaporator thickness, overcoming the limitations of traditional template casting and freeze-drying processes. This method enables the efficient production of integral self-floating evaporators with complex geometries.
[0089] The optimized evaporator PDHF-6%ACAT-F(84) can achieve a surface temperature of 55°C and an evaporation rate of 2.93 kg·m³ under a single daylight exposure. -2 ·h -1 The efficiency reached 95.11%. The device operated continuously for 30 days without salt precipitation, demonstrating stable performance. Particularly noteworthy is the ability to recycle the PDHF-6%ACAT material by controlling the crosslinking density through a UV curing process. Analysis after recycling confirmed that the material's molecular structure, thermal properties, and mechanical properties remained essentially unchanged. The recycled material was successfully 3D printed into solar interface evaporators (SGIEs), whose evaporation performance was almost identical to the original device. This invention achieves a synergistic integration of high efficiency, salt resistance, and closed-loop recycling, laying an important technical foundation for large-scale solar-driven interface water evaporation technology.
[0090] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a cyclic olefin polymer-based flexible printing filament, characterized in that, Includes the following steps: A ring-opening polymerization reaction of cyclic olefin monomers was catalyzed by a Grubb catalyst to form a cyclic olefin polymer. The mixture of the cyclic olefin polymer and the filler material was cured by ultraviolet light under the action of a photoinitiator to obtain a cyclic olefin complex. The cyclic olefin complex was then extruded by screw extrusion to prepare a cyclic olefin polymer-based flexible printing filament. The filler material is at least one of amino-terminated aniline trimer, carbon black, graphite, carbon nanotubes, graphene, and silicon dioxide.
2. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 1, characterized in that, The cyclic olefin monomer is at least one selected from 2,3-dihydrofuran, 2,5-dihydrofuran, dicyclopentadiene, cyclooctene, and cyclooctadiene.
3. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 1, characterized in that, The filler material accounts for 0.5% to 40% of the molar percentage of the cyclic olefin monomer.
4. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 1, characterized in that, The Grubbs catalyst is a Grubbs I catalyst, a Grubbs II catalyst, or a Grubbs III catalyst; the amount of Grubbs catalyst used is one part per ten thousand to ten percent of the molar percentage of the cyclic olefin monomer.
5. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 1, characterized in that, The specific preparation method of the cyclic olefin complex is as follows: Grubb catalyst was dissolved in an organic solvent and then mixed with a mixture containing a photoinitiator and cyclic olefin monomers. The cyclic olefin monomers underwent ring-opening polymerization catalyzed by the Grubb catalyst at 0℃~100℃ to form a cyclic olefin polymer. Organic solvent and filler were added and mixed evenly to obtain a mixture. The mixture was then cured under ultraviolet light in the presence of a photoinitiator to obtain a cyclic olefin complex.
6. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 5, characterized in that, The wavelength of the ultraviolet light is 350nm to 420nm, and the curing time of the ultraviolet light is 0.001h to 72h.
7. The method for preparing the cyclic olefin polymer-based flexible printing filament according to claim 5, characterized in that, The organic solvent is at least one of tetrahydrofuran, dichloromethane, and N,N-dimethylformamide; the photoinitiator is any one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. The amount of photoinitiator is 0.05% to 5% of the molar percentage of the cyclic olefin monomer.
8. A cyclic olefin polymer-based flexible printing filament, characterized in that, The cycloolefin polymer-based flexible printing filament is prepared using the method described in any one of claims 1 to 7.
9. A solar interface evaporator, characterized in that, The solar interface evaporator is prepared by fused deposition modeling (FDM) using the cyclic olefin polymer-based flexible printing filament as described in claim 7.
10. The solar interface evaporator according to claim 9, characterized in that, The solar interface evaporator has a gradient pore structure, and the pore tilt angle of the gradient pore structure is 0° to 90°.
